PENGARUH HARGA, PENILAIAN PRODUK, DAN CASHBACK TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE (Studi Kasus Mahasiswa Universitas Islam Syekh-Yusuf Tangerang) - Wanda Yulia Utami (Juremi: Jurnal Riset Ekonomi, 2024)
This study aims to determine the effect of Price (X1), Product Valuation (X2), and Cashback (X3) on purchase decisions (Y) on the shopee marketplace. This research was conducted with quantitative research methods with survey methods, namely research that focuses on testing hypotheses with statistical method analysis too and producing generalizable conclusions. The sample in this study was Sheikh-Yusuf Islamic University students as consumers of the Shopee marketplace totaling 100 people. The sample of respondents in this study used a causal associative approach method with a purposive sampling procedure. While the sampling method of this study uses the Slovin formula. Data analysis techniques with validity tests, reliability tests, classical assumption tests, multiple correlation analysis, simple correlation analysis, multiple linear regression analysis, and hypothesis tests. The calculation process uses SPSS 25. The test results show that Price has a positive and significant effect on purchase decisions by 75.9%, Product Valuation has a positive and significant effect on purchase decisions by 75.1%, and Cashback has a positive and significant effect on purchase decisions by 67.2% in the marketplace Shopee. And price, product valuation, and cashback together have a positive and significant effect on purchasing decisions by 83.6%. A factor that greatly influences purchasing decisions on the shopee marketplace is product assessment